(untitled) (Research, Society and Development, 2021)
In the end of 2019, in the city of Wuhan, the first case of COVID-19 emerged, after that, the cases increased and reached the other countries, giving rise to the current pandemic. The neurophysiology of fear is defined by a chain reaction, with the involvement of several anatomical regions of the brain, responsible for different functions, which characterize the behavior of something unknown. The Burnout syndrome is a psychic disorder, depressive, developed in up to 74% of nurses, due to extreme exhaustion at work. Objective: To research, to describe and to identify risk factors that contribute to the development of Burnout syndrome in nurses, working in emergency care units. Addressing the neurophysiological confrontation of fear in the face of the COVID-19 pandemic. To describe the psychotherapeutic and pharmacotherapeutic importance. Method: This is a qualitative and descriptive bibliographic review. The studies took place in April and May 2021. The articles were extracted from search engines such as: Lilacs (Latin American and Caribbean health sciences literature), Scielo (Scientific Electronic Library Online), Pebmed and Google Scholar. 33 scientific articles and 4 books were used through the descriptors: Nurse; Pharmacotherapy; Neurophysiology and Psychotherapy. Results: Numerous risk factors were found, associated with the behavior and nature of depressed mood, which predisposes to risks for professional nurses to develop the Burnout syndrome. Conclusion: Many risk factors could be reduced. Psychotherapeutic monitoring, associated with pharmacotherapy, is essential. The use of antidepressants provides stabilization of depressed mood, which favor the clinical outcome in the face of the diagnosis of Burnout syndrome.